The Choice of a Profession by Blind Senior Students and their Relevance to the Labor Market - Komova N.S.,; Sokolov V.V., (Психолого-педагогические исследования, 2018)
This article presents results of the research on the professional orientation and employment of blind graduates of schools in six regions of the Russian Federation specialising in teaching children with visual impairments. Also analysis related to the situation with the employment of people with visual disabilities are given. This analysis are based on information from Russian Association Of The Blind. Reasons of low rates of the employment of young people with disabilities are shown. The dependence of the awareness of the choice of the profession by the blind during the period of school education on specifics of the organisation of vocational guidance work for children with visual impairments, as well as on the level of maturity of the personality and personal qualities of students is presented. The ways of overcoming the reasons negatively affecting the results of career guidance work and the employment of graduates of special schools are indicated. Examples of effective career guidance work and successful employment of young people with visual deprivation are given. The article is Amed at researchers involved in education of children with visual disabilities, organisers of career guidance work, tiflopedagogs and parents who have blind children.